2008
DOI: 10.1080/07373930801898125
|View full text |Cite
|
Sign up to set email alerts
|

Method to Characterize the Air Flow and Water Removal Characteristics During Vacuum Dewatering. Part II—Analysis and Characterization

Abstract: This is part II of a study reported earlier on a method to characterize the air flow and water removal characteristics during vacuum dewatering. This article presents experimental data and analysis of results from the use of a cyclically actuated vacuum dewatering device for removing moisture from wetted porous materials such as paper with the intermittent application of vacuum and accompanying air flow though the material. Results presented include sheet moisture content as a function of residence time and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The overarching conclusion from earlier work is that the dewatering behavior of the vacuum suction boxes is consistent with the overall dewatering behavior of the papermaking process, with easy dewatering in the early parts and increasingly harder to remove water, diminishing returns (Attwood 1962;Neun 1994Neun , 1996Räisänen et al 1996;Ramaswamy 2003;Pujara et al 2008). The location of water within the sheet's structure is the reason why it becomes increasingly difficult to dewater.…”
Section: Stenström and Nilsson 2015mentioning
confidence: 67%
See 1 more Smart Citation
“…The overarching conclusion from earlier work is that the dewatering behavior of the vacuum suction boxes is consistent with the overall dewatering behavior of the papermaking process, with easy dewatering in the early parts and increasingly harder to remove water, diminishing returns (Attwood 1962;Neun 1994Neun , 1996Räisänen et al 1996;Ramaswamy 2003;Pujara et al 2008). The location of water within the sheet's structure is the reason why it becomes increasingly difficult to dewater.…”
Section: Stenström and Nilsson 2015mentioning
confidence: 67%
“…Showed diminishing returns for the dryness development. Pujara et al 2008 Described a new apparatus for studying deformation of the sheet during and after vacuum dewatering. The sheets are shown to be noticeably compressed due to the pressure drop during vacuum dewatering and they expand afterwards.…”
Section: Ramaswamy 2003mentioning
confidence: 99%
“…There are of course other experimental data that describe dewatering with vacuum. They were considered to be part of the model fitting but excluded for the following reasons: For Pujara et al [26] and Attwood, [16] water retention values were not found. Åslund et al [27] and R€ ais€ anen [18] used a factor 10 longer dwell times than the other data, while Kullander et al [28] had a factor 10 shorter dwell times.…”
Section: Moisture Ratio Model Kerekes and Mcdonaldmentioning
confidence: 99%
“…[9][10][11] Vacuum compresses the wet web, while displacement dewatering occurs when the air flows through the wet web and drives the water out of interfiber voids. [9,[11][12][13][14][15][16][17][18] The main limiting factors of dewatering are permeability, compressibility of the wet web and the surface tension of water. These properties are affected by factors such as basis weight, consistency, refining, temperature, fibers flocculation, fines content and vacuum level.…”
Section: Introductionmentioning
confidence: 99%